2019
DOI: 10.15252/embj.201899299
|View full text |Cite
|
Sign up to set email alerts
|

ROCK 2 inhibition triggers the collective invasion of colorectal adenocarcinomas

Abstract: The metastatic progression of cancer is a multi‐step process initiated by the local invasion of the peritumoral stroma. To identify the mechanisms underlying colorectal carcinoma (CRC) invasion, we collected live human primary cancer specimens at the time of surgery and monitored them ex vivo. This revealed that conventional adenocarcinomas undergo collective invasion while retaining their epithelial glandular architecture with an inward apical pole delineating a luminal cavity. To identify the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 103 publications
1
37
1
Order By: Relevance
“…The low-contractile-force phenotype differs from the view that contractile tension increases with cell transformation in cancer (Paszek et al, 2005) and that a higher rigidity of the extracellular environment and a high-contractile-force phenotype favor cell invasiveness (Butcher et al, 2009;Kraning-Rush et al, 2012;Mierke et al, 2011). Rather, our results suggest that the relaxation of contractile forces is associated with cell scattering and migration, as it has been observed in HMECs with super-numerary centrosomes that form invasive structures in 3D cultures (Godinho et al, 2014), in cells at the front of invasive colorectal carcinomas (Libanje et al, 2019) or in metastatic osteosarcoma cells (Holenstein et al, 2019). By contrast, a high-contractile-force phenotype is more likely to promote primary tumor growth, cell survival in circulation, and at a secondary site, cell adhesion, aggregation, and the formation of a metastatic tumor (Rodriguez-Hernandez et al, 2016;Tavares et al, 2017).…”
Section: The Initiation Of Emt and Establishment Of The Intermediate contrasting
confidence: 68%
“…The low-contractile-force phenotype differs from the view that contractile tension increases with cell transformation in cancer (Paszek et al, 2005) and that a higher rigidity of the extracellular environment and a high-contractile-force phenotype favor cell invasiveness (Butcher et al, 2009;Kraning-Rush et al, 2012;Mierke et al, 2011). Rather, our results suggest that the relaxation of contractile forces is associated with cell scattering and migration, as it has been observed in HMECs with super-numerary centrosomes that form invasive structures in 3D cultures (Godinho et al, 2014), in cells at the front of invasive colorectal carcinomas (Libanje et al, 2019) or in metastatic osteosarcoma cells (Holenstein et al, 2019). By contrast, a high-contractile-force phenotype is more likely to promote primary tumor growth, cell survival in circulation, and at a secondary site, cell adhesion, aggregation, and the formation of a metastatic tumor (Rodriguez-Hernandez et al, 2016;Tavares et al, 2017).…”
Section: The Initiation Of Emt and Establishment Of The Intermediate contrasting
confidence: 68%
“…Our results also appear in apparent contradiction with those obtained by Vishnubhotla and collaborators who reported that ROCK-2 was highly expressed in SW620 colon cancer cells, mainly distributed in invadopodial-like structures and that its knock-down reduced the depth of invasion into a 3D-scaffold of type I collagen 61 . However, our results are in line with those recently reported by Libanje and collaborators who demonstrated that colorectal cancer cells mainly harbour a collective mode of invasion and that ROCK-2 inhibition triggers the initial induction of leader cell formation and induces collective invasion from cysts 62 . Therefore, these apparently contrasting results should probably be studied with regard to the different growing modes and environmental conditions (2D vs 3D, type and stiffness of the extracellular matrix, etc.)…”
Section: Discussionsupporting
confidence: 93%
“…Cancer organoids have also been used to model metastatic processes, in particular to investigate the different processes of invasion [164,165]. For example, a study conducted on CRC organoids showed that inhibition of rho-associated protein kinase 2 (ROCK2) improved collective invasion in its early stages [166].…”
Section: Organoids As a Model To Study Tumorigenesismentioning
confidence: 99%